2004
DOI: 10.1089/0892779041271689
|View full text |Cite
|
Sign up to set email alerts
|

Reflux of a Staple after Kock Pouch Urinary Diversion: A Nidus for Renal Stone Formation

Abstract: A patient with cystectomy and urinary diversion after spinal cord injury had multiple pouch concretements and a kidney stone formed around a staple that apparently had refluxed from the nipple of the pouch. In such cases, the stone and staple should be removed at the same time, either percutaneously or by ureterorenoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Massoud[ 16 ] also reported that a metal surgical clip was displaced into the ureter after open partial nephrectomy (OPN), all of which was passed spontaneously. Furthermore, in the urologic literature, it has been reported that surgical clips, and even absorbable gastrointestinal staples, can act as a nidus for stone formation when in contact with urine[ 17 ]. Msezane et al [ 18 ] reviewed differing sealants and laparoscopic instruments that can be used to stop bleeding of the renal parenchyma within LPN and concluded that there is no gold-standard single agent or combination of products that can be applied to all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Massoud[ 16 ] also reported that a metal surgical clip was displaced into the ureter after open partial nephrectomy (OPN), all of which was passed spontaneously. Furthermore, in the urologic literature, it has been reported that surgical clips, and even absorbable gastrointestinal staples, can act as a nidus for stone formation when in contact with urine[ 17 ]. Msezane et al [ 18 ] reviewed differing sealants and laparoscopic instruments that can be used to stop bleeding of the renal parenchyma within LPN and concluded that there is no gold-standard single agent or combination of products that can be applied to all cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few case reports have described intravesical migration of Weck Hem-o-lok clips leading to stone formation after radical prostatectomy [5, 6]. Other reports have shown that staples used during cystectomy and urinary diversions may also cause stone formation when they are in direct contact with urine [7]. Furthermore, in an investigation of various suture materials in the bladder wall of rats, Kosan et al found that the duration of contact between foreign body and urine was the greatest predictor of stone formation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic complications may occur in patients with urinary intestinal diversion as a result of the resorption of urinary solutes across the bowel segment, including serum electrolyte abnormalities, bony demineralization and calculus formation [1,2,3,4,5,6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%